RANCANG BANGUN SISTEM INVENTORY ATK DAN BARANG CETAKAN BERBASIS WEB PADA BSI KCP MEDAN KRAKATAU - Rozai Iskandar; Miranda Miranda (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Bank Syariah Indonesia KCP Medan Krakatau is one of the branch financial institutions of PT Bank Syariah Tbk based on micro-sharia principles. The activities at the branch office certainly require office supplies and printed materials to support work activities. The operational staff's activities in recording office supplies and printed materials still use manual methods, resulting in suboptimal reporting of office supplies and printed materials. This research aims to design a web-based inventory system for office supplies and printed materials with the implementation of the waterfall method. In the design of this system, it is expected to help provide information about reports and stock of office supplies and printed materials. This, in turn, can assist and expedite the reporting process for the use of office supplies and printed materials, reducing inaccuracies in information and generating detailed and effective reports.